Analytical study on influence of subsurface voids on moment capacity of singly reinforced concrete beam – Inspired by a project case study. (May 2023) - Li, Zhengqi
Abstract: Ultrasonic echo tomography is a non-destructive testing technique that has been used to detect subsurface construction defects located within reinforced concrete members. In order to reasonably define the scope of the repair work for the detected subsurface construction defects, it is important to understand the relationship between the extent of the construction defects and the performance of structural members. This preliminary analytical study was conducted to evaluate the moment capacity of singly reinforced concrete beam sections containing subsurface voids. It was determined in this study that if the location of void remained the same, an increase in the depth of void resulted in a reduction in the moment capacity. As the void extended outside the compression zone and the depth of void continued to increase, the moment capacity did not decrease further. If the depth of void remained the same, a void located closer to the top of beam resulted in more reduction in the moment capacity than the same void located closer to the neutral axis. A parameter named the percentage of remaining moment capacity was proposed to be used to identify the unacceptable void configurations from the standpoint of moment capacity.